2019
DOI: 10.1080/02670844.2018.1524036
|View full text |Cite
|
Sign up to set email alerts
|

FeCrNiMnAl high-entropy alloy coating by spray deposition and thermite reaction

Abstract: High-entropy alloy (HEA) coatings demonstrate excellent corrosion resistance and wear resistance. However, their applications are limited owing to a complicated process and high costs. In the present work, an FeCrNiMnAl HEA coating was synthesised by spray deposition combining with thermite reaction using a mixture of Fe 2 O 3 , CrO 3 , MnO 2 , Ni, and Al powders as precursors. After spray deposition, the as-formed coating layer consisted of two bodycentred cubic phases, and showed good metallurgical bonding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…HEAs have four main effects [7]: the high entropy effect [8,9], the lattice distortion effect [10,11], the sluggish diffusion effect [12], and the cocktail effect [13,14]. They have at least five elements and each element's composition ranges from 5 to 35 at-%.…”
Section: Introductionmentioning
confidence: 99%
“…HEAs have four main effects [7]: the high entropy effect [8,9], the lattice distortion effect [10,11], the sluggish diffusion effect [12], and the cocktail effect [13,14]. They have at least five elements and each element's composition ranges from 5 to 35 at-%.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high mixing entropy effect, HEAs intend to form stable solid solutions such as BCC, FCC, or FCC+BCC structure [2][3][4]. Due to the four 'core effects' of high entropy, namely high entropy, sluggish diffusion, severe lattice distortion, and cocktail effects, HEAs exhibit some superior mechanical properties such as high hardness, strength, and ductility [5], exceptional thermal stability [3], excellent oxidation resistance at high temperature, good wear-resistant properties, and corrosion resistance, therefore HEAs become attractive materials for the modern industrial applications [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Joseph et al [1] observed the wear rate of Al 0.3 CoCrFeNi remains constant above 600 °C, which was attributed to the strengthening effect of B2 precipitates. Chen et al [5] found that FeCrNiMnAl HEAs coating had a microhardness value of 432.2 HV, which had a lower friction coefficient compared with the substrate by the 0.55 and exhibited superior wear resistance. As less is still known about the wear properties of FeCrNiMnAl series HEAs, the present work aims to study as-cast microstructure, mechanical and wear properties of the FeMnCrNiAl x HEAs changed with Al contents.…”
Section: Introductionmentioning
confidence: 99%